Dilematika “Keadaan Tertentu” Dalam Penjatuhan Sanksi Pidana Mati Terhadap Koruptor di Indonesia - Natasha Intania Sabila; Maharani Qaulan Syadidah Az Zahro; Balilah Rizki Putriga (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
Phrase certain conditions are regulated by law as one of the reasons for imposing the death penalty on corruptors. Emergency management funds. As a serious crime, the threat of the death penalty for corruptors still leaves a variety of discourse between pro- and con-parties. This article aims to examine the consequences of death penalty sanctions in certain circumstances in terms of the effectiveness of imposing punishment on corruptors. This study uses normative legal methods. Data was callected from legal and statutory literature. The research results show that there are still multiple interpretations of the phrase